2010
DOI: 10.1002/jsfa.4140
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, antioxidant and antibacterial properties of the essential oils of Etlingera elatior and Cinnamomum pubescens Kochummen

Abstract: This study suggests that the essential oils from Cinnamomum pubescens Kochummen and Etlingera elatior could be potentially used as a new source of natural antioxidant and antibacterial in the food and pharmaceutical industries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
38
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 19 publications
6
38
0
5
Order By: Relevance
“…This result is similar in other plant species (Nurain et al, 2013); but contradicted with the EE essential oil study reported earlier (Abdelwahab et al, 2010). Different results obtained could be due to the plant maturity, seasons and geographical locations of the different of plant materials collected (Çetinkaya et al, 2016).…”
Section: Resultssupporting
confidence: 43%
See 1 more Smart Citation
“…This result is similar in other plant species (Nurain et al, 2013); but contradicted with the EE essential oil study reported earlier (Abdelwahab et al, 2010). Different results obtained could be due to the plant maturity, seasons and geographical locations of the different of plant materials collected (Çetinkaya et al, 2016).…”
Section: Resultssupporting
confidence: 43%
“…However, according to literature, there was only one study that had reported on the antioxidant properties from the EE essential oil (Abdelwahab et al, 2010) while no exploration was done on the photo-protective activity. Exploring photo-protective activity from herbal plant resources has been gaining increasing attention in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Staphylococcus aureus (Ghasemzadeh et al, 2015, Wijekoon et al, 2013, Abdelwahab et al, 2010, Lachumy et al, 2010, Naufalin et al, 2005. Namun, identifikasi komponen aktif antibakteri dari bunga kecombrang belum dilakukan.…”
Section: Pendahuluanunclassified
“…1 Following this scheme in Tab. 1, apple jam (JA), pumpkin (JP) and apple, pumpkin and cinnamon jam (JAPC) were prepared.…”
Section: Raw Materialsmentioning
confidence: 99%